What's at stake of normalized relations between the United States and Iran - Matějková, Adéla (2013)
This thesis tries to identify what's at stake of normalized relations between the United States and Iran since the Iranian revolution in 1979. The thesis tries to find out what are the key issues behind the failed relations between these two countries from the American point of view in order to determine whether normalized relations between these two countries can ever be achieved. It elaborates on four key characteristics of individual level analysis of foreign policy decision making applied on three key Presidents involved in foreign policy making towards Iran since 1979.